STRATEGI GURU DALAM MEMBANGUN SIKAP MANDIRI BAGI SISWA BERKEBUTUHAN KHUSUS DI SEKOLAH LUAR BIASA AL IKHSAN BAGOR NGANJUK - Fauzi'ah, Novita Fairuz; Listyaningsih, Listyaningsih (Kajian Moral dan Kewarganegaraan, 2024)
This research describes the strategies used by teachers at the Al Ikhsan Bagor Nganjuk Special School for students with special needs. The targets of this research were students with autistic disabilities who were in grade 5 of elementary school. This is because students with autistic disabilities are the students with the most disabilities at the elementary school level, namely in grade 5 of elementary school. The theory used in this research is the Behavioristic Classical Conditioning Theory developed by Ivan Petrovich Pavlov. The approach used in this research is qualitative with descriptive analysis methods. This research took informants from teachers at the Al Ikhsan Bagor Special School as research subjects. The data collection techniques used were observation, in-depth interviews and documentation. The validity test of the data used is source triangulation. The results of the research show that the strategies used by Al Ikhsan Bagor Nganjuk Special School teachers are: (1) through giving appreciation. Giving appreciation can be done in two ways, namely first in the form of gestures or body movements such as giving applause when students successfully complete an activity. Second, in verbal form or words such as words of encouragement, you are great, you are extraordinary (2) through games. Play activities are one of the factors that can stimulate students' sensory, motoric and cognitive development, such as puzzle games, throwing balls, attaching body parts and coloring